Promoting the Patriotic Agenda on Social Media among Russian Students - R. V. Parma (Moscow Polytechnic University, 2024)
The study aims to compare patriotic attitudes among the social group of student youth, as reflected in public opinion dynamics and social media information flows. The research methodology was based on cognitive and network approaches to examining social processes. The methods of open sociological and statistical data analysis, cognitive content mapping and automated social media analysis were used to determine the content and intensity of the impact of opposing patriotic and anti-patriotic information flows in the Russian segment of social media on the social values and attitudes of student youth. The results of the study revealed a high intensity of information pressure of anti-patriotic information flow in the digital communications environment on the audience of student youth. The sociological data indicates a strong prevalence of patriotic attitudes among the youth, however, analysis of information flows reveals the widespread presence of anti-patriotic narratives and discourses on social networks. The student communities of supporters of the patriotic idea differ from the opponents in that they are much more numerous, but much less active in producing and promoting semantic content in the social media space. The social media segment in Russia lacks a well-developed network infrastructure, including opinion leaders and effective platforms for broadcasting patriotic content. The empirical study of information flows has shown that universities are not on the list of platforms for promoting the patriotic agenda. Russian universities face a significant challenge in implementing patriotic education for the youth due to their technological and ideological detachment from students who are immersed in the digital communication environment. These circumstances reveal institutional issues with implementing the state policy of youth development in the face of existential challenges.